Pengaruh Perbedaan Waktu Towing pada Alat Tangkap Jaring Insang (Gill Net) terhadap Hasil Tangkapan Ikan Kakap Putih (Lates Calcarifer) di Perairan Gisik Cemandi Sidoarjo - Chytline Canisha Praftono; Exist Saraswati; Yusrudin Yusrudin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
In fishing, the majority of the Gisik Cemandi villagers use gill nets as fishing gear, which also affects the catch of white snapper. The practice of pulling nets at different times can produce different catches. The purpose of this research is to identify the composition of the gillnet catch. And to analyze the effect of differences in towing time on the gillnet catch. And to find out the optimal towing time in catching white snapper using gillnet fishing gear. Data analysis uses statistical analysis using Analysis of Variance (ANOVA) and Normality to ensure that the data analyzed is appropriate. To see whether or not there is an effect of the soaking time, if there is a significant effect, the statistical analysis is continued with the BNT Test for the soaking time with which time gives the best white snapper catch. These results indicate that there is a significant difference in the catch variable between the 4-hour treatment with 3 hours and 2 hours.